2019
DOI: 10.1002/ajoc.201900300
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling Reaction of Dimer‐Derived Persistent Tertiary‐Carbon‐Centered Radicals with Azo Compounds

Abstract: Cross-coupling reactions using tertiary carboncentered radicals are an important class of transformations for constructing C(sp 3 )À C(sp 3 ) bonds, but the use of dimers as precursors of the persistent radicals is quite rare. Herein, we describe a radical-based cross-coupling reaction between dimers (prepared from 2-oxindoles and benzofuranones) and azo compounds that proceeds simply upon heating the reaction mixture. We present a conformational analysis of the dimers and we characterize the generation of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…to 1) in toluene after replacing O 2 with Ar, according to a previously developed procedure. 8,9) As we expected, upon heating the reaction mixture to 100°C, we obtained the cross-coupling adducts 5 in reasonable yields. Benzofuranones 1a, 1b and 1c are efficiently transformed to the corresponding cross-coupling adducts (5aa: 69%, 5ba: 64%, 5ca: 52%) with the use of AIBN (3a: azobisisobutyronitrile) 32) as a precursor of the transient radical.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…to 1) in toluene after replacing O 2 with Ar, according to a previously developed procedure. 8,9) As we expected, upon heating the reaction mixture to 100°C, we obtained the cross-coupling adducts 5 in reasonable yields. Benzofuranones 1a, 1b and 1c are efficiently transformed to the corresponding cross-coupling adducts (5aa: 69%, 5ba: 64%, 5ca: 52%) with the use of AIBN (3a: azobisisobutyronitrile) 32) as a precursor of the transient radical.…”
Section: Resultssupporting
confidence: 83%
“…[12][13][14] We initiated this study with use of racemic Pd complex I as a catalyst for the proposed aerobic dimerization of 1 because the C(sp 3 )-C(sp 3 ) bond in 2 is readily cleavable even at room temperature, providing thermodynamically stable meso-2, rather than dl-2, as the major product. 8) We found that the use of CH 3 CN as the solvent is critical to obtain a high yield of meso-2a (Table 1, entry 1 vs. entry 2). When we examined the reaction of 1a in the presence of Pd complex I (5 mol%) under an oxygen atmosphere in tetrahydrofuran (THF), which is a standard solvent for acid-base catalysis with I, 21) benzofuranone 1a was recovered in 94% yield (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…These bond strengths infer radical intermediates that are dynamically stable causing them to display reactivity profiles consistent with persistent radicals . This family of radical intermediates tends to be less reactive by comparison to short‐lived transient radicals . We hypothesize that radicals formed in this reaction display low reactivity, prolonging their lifetimes thus enabling them to potentially diffuse into the enzyme active site for radical termination by flavin if they are initially formed in solution.…”
Section: Figurementioning
confidence: 99%